Comment on Tomaskova et al. Mortality in Miners with Coal-Workers' Pneumoconiosis in the Czech Republic in the Period 1992-2013. Int. J. Environ. Res. Public Health, 2017, 14, 269 - Yong, Mei (International journal of environmental research and public health, 2018)
With interest, I read the recent analysis by Tomaskova and co-workers (2017) about mortality from coal workers' pneumoconiosis (CWP). The research question remains unclear whether coal workers' pneumoconiosis (CWP) resulting from exposure to respirable coal dust containing crystalline silica accelerates the development of lung cancer or whether it is an intermediate stage in the pathway. I made several points of considerations with respect to (1) qualified data; (2) alternate measures for excessive risks; and (3) methodological flaws that should be avoided.
Keywords: Anthracosis; pneumokonióza; lung cancer; prach; antrakóza; Pneumoconiosis; Dust; Humans; uhlí; Česká republika; Coal Mining; lidé; Czech Republic; coal workers’ pneumoconiosis (CWP); Coal; těžba uhlí